Phonological Description of the Spoken English Forms of Educated Ikale and Ondo Speakers of Nigerian English (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Attention of researchers has been drawn to the phonological description of the varieties of Nigerian English spoken by the three major ethnic groups such as the Yoruba, Hausa and Igbo. However, as Jowitt (1991:71) comments, there is little available information on the spoken English of Nigeria’s smaller ethnic groups. Therefore, this study undertakes a phonological description of the spoken English forms of educated Ikale and Ondo speakers of Nigerian English. Guided by Generative Phonology and Metrical Phonology as theoretical frameworks, one hundred educated subjects from each of Ikale and Ondo were used to collect data for the research. The subjects were made to read a prepared text containing the features being tested into a voice recorder. Their responses were transcribed and statistically analyzed. Both the voiced and the voiceless dental fricatives /ð/ and /θ/ still pose a challenge to the educated people from Ikale and Ondo dialectal groups. Most of the English vowels used by educated Ikale and Ondo speakers of Nigerian English in their spoken English are hardly approximated to those of Standard English; this low performance confirms the results of earlier researches. It was observed by this research that the spoken English of educated Ikale and Ondo speakers of Nigerian English is at variance with Standard English in terms of stress placement, articulation of some vowels and consonant sounds. It was also found that the spoken English of educated Ikale and Ondo is characterized by spelling pronunciation. In conclusion, the outright absence of the English phonological process of assimilation from the spoken English of educated Ikale and Ondo English speakers has a telling effect on their phonological renditions; hence, breeding a version of Nigerian English which could either be seen as variation or deviation from Standard British English.
Keywords: Phonological Description; Spoken English; Generative Phonology; Metric Phonology and Nigerian English